Vitamin E in the prevention of vancomycin-induced nephrotoxicity - Rasool Soltani; Farzin Khorvash; Mohsen Meidani; Shirinsadat Badri; Sajedeh Alaei; Shahram Taheri (Wolters Kluwer Medknow Publications, 2020)
Background and purpose: The use of vancomycin, as a key therapeutic choice for treatment of hazardous infections, may be associated with nephrotoxicity. The proposed mechanism is the indirect production of reactive oxygen species and oxidative stress. The purpose of this study was to investigate the effect of vitamin E asan antioxidant agent in the prevention of vancomycin-induced nephrotoxicity. Experimental approach: In a matched-groups interventional study, patients who received vancomycin for any indication were assigned to vitamin E (n = 30) and control (n = 60) groups. The patients in experimental group received 400 units of oral vitamin E per day for 10 days started concurrently with vancomycin, while the patients in control group received vancomycin alone. Serum level of creatinine, blood urea nitrogen (BUN), creatinine clearance (CrCl), and 24-h urine output were determined and recorded before the start of interventions, every other day during therapy, and 12 h after the last dose of vancomycin in 10[th] day of therapy for all patients. Also, the rate of acute kidney injury (AKI) in the two groups was recorded. Finally, the mean values of the measured parameters were compared between the groups. Findings / Results: Treatment with vitamin E for 10 days resulted in a significant reduction of BUN (from 17.5 ± 7.8 mg/dL at baseline to 11.4 ± 4.8mg/dL at the end; P < 0.001) along with slightly non-significant increase of CrCl (from 84.7 ± 18.9 mL/min at baseline to 91.3 ± 19.5 mL/min at the end; P = 0.301) in comparison to the control group. However, CrCl decreased significantly in the control group. Vitamin E had no significant effect on24-h urine output. Regarding vancomycin-induced AKI, 12 cases were observed in the control group, while no case was reported in experimental group (P = 0.041). Conclusion and implications: This study showed the beneficial effect of add-on therapy of vitamin E besides vancomycin in reducing AKI, which could be considered as a new potential prophylactic therapy for vancomycin-induced nephrotoxicity.